Kepemimpinan Berbasis Budaya Religius di MI Terpadu Al-Ishlah Gorontalo - Sintyawati Kaaba; Kadim Masaong; Arwildayanto Arwildayanto (Pedagogi: Jurnal Ilmu Pendidikan, 2018)
This study aims to describe: (1) preparation of religious culture-based school programs, (2) implementation of religious culture-based activities, (3) values applied in religious culture-based leadership, and (4) habituation of school community in implementing the religious culture. This study used a qualitative approach with a case study. Data were collected using observation, interview, and documentation. Data were analyzed by using an interactive model; data reduction, data presentation, and conclusions. Checking the validity of data extends the presence of researchers in the study sites, deep observation, triangulation of sources and researcher’s methods/techniques and member check. The results show: (1) preparation of religious culture-based school programs such as the principal planning early in the semester to create a program of school activities involving school personnel, such as teachers and staffs, (2) implementation of religious culture-based activities, such as daily program, weekly program and annual program involving the teachers, students, parents and government, (3) values applied such as the value of religiosity, value of nationalism, value of independence, value of integrity and value of mutual cooperation, and (4) habitation of school community by doing murojaah the memorization (repeating the memorization), fasting on Tuesday and Thursday, liqa (mentoring), pray for Dhuha, pray for Dzuhur, etc.